2016
DOI: 10.1080/14397595.2016.1249537
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of bone marrow for TAFRO syndrome

Abstract: We report two cases of TAFRO syndrome, which is characterized by thrombocytopenia, anasarca, fever, renal insufficiency, and organomegaly. Magnetic resonance imaging (MRI) of the spine showed a dark medullary pattern in the bone marrow on the T1- and T2-weighted images of both patients. One patient showed complete resolution after treatment. Serial MRIs of the improved patient revealed a transition to a normal marrow pattern on both images, which might represent resolution of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…After a thorough review of histopathological descriptions for the 20 cases: 4 MPGN-like patients seems to be a great deal of overlap between TMA (absence of immune complex deposits), 2 patients presented MPGN with straight deposits for which it is difficult to conclude in favor of a TMA (but without it being incompatible), 9 patients presented more argument in favor of TMA and 5 patients for which the details of the renal biopsy is not available (Table 1). One previous report speculates that renal histology in the early stages of TAFRO syndrome may begin with endotheliosis and glomerular double-contours, which are consistent with histopathology of TMA (19). Since we didn't find any etiology to explain MPGN, we suspect that there is a histopathological and probably physiopathology continuum between TMA and MPGN.…”
Section: Discussionmentioning
confidence: 56%
“…After a thorough review of histopathological descriptions for the 20 cases: 4 MPGN-like patients seems to be a great deal of overlap between TMA (absence of immune complex deposits), 2 patients presented MPGN with straight deposits for which it is difficult to conclude in favor of a TMA (but without it being incompatible), 9 patients presented more argument in favor of TMA and 5 patients for which the details of the renal biopsy is not available (Table 1). One previous report speculates that renal histology in the early stages of TAFRO syndrome may begin with endotheliosis and glomerular double-contours, which are consistent with histopathology of TMA (19). Since we didn't find any etiology to explain MPGN, we suspect that there is a histopathological and probably physiopathology continuum between TMA and MPGN.…”
Section: Discussionmentioning
confidence: 56%
“…Steroid was used in 18 cases (94.7%), and mPSL pulse therapy was used in 17 cases (89.5%). Only 5 cases (26.3%) were successfully treated with steroid therapy alone [28,43,49,52]. It should be noted that almost all cases (84.2%) required HD within three weeks of admission.…”
Section: Discussionmentioning
confidence: 99%
“…An anterior mediastinal lesion could be associated with the etiology of TAFRO syndrome, and fibrous changes might correspond with inflammatory reactions associated with hypercytokinemia. Nakamura et al reported diffuse hypointensity of the bone marrow in T1-and T2-weighted magnetic resonance images in patients with TAFRO syndrome, and they assumed that these findings reflected a reduction in the fatty component corresponding to reconversion into hematopoietic marrow owing to anemia and thrombocytopenia [28]. Behnia et al mentioned the efficacy of FDG-PET for selecting a lymph node for biopsy, for ruling out malignancies, and for evaluating treatment response [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations